Sufi institutions (Leiden ; Boston)
xv, 442 sayfa
Keywords: “This volume describes the social and practical aspects of Islamic mysticism (Sufism) across centuries and geographical regions. Its authors seek to transcend ethereal, essentialist and “spiritualizing” approaches to Sufism, on the one hand, and purely pragmatic and materialistic explanations of its origins and history, on the other. Covering five topics (Sufism’s economy, social role of Sufis, Sufi spaces, politics, and organization), the volume shows that mystics have been active socio-religious agents who could skillfully adjust to the conditions of their time and place, while also managing to forge an alternative way of living, worshiping and thinking. Basing themselves on the most recent research on Sufi institutions, the contributors to this volume substantially expand our understanding of the vicissitudes of Sufism by paying special attention to its organizational and economic dimensions, as well as complex and often ambivalent relations between Sufis and the societies in which they played a wide variety of important and sometimes critical roles“ --